2007
DOI: 10.4315/0362-028x-70.4.952
|View full text |Cite
|
Sign up to set email alerts
|

Development of Thermal Surrogate Microorganisms in Ground Beef for In-Plant Critical Control Point Validation Studies

Abstract: In search of a suitable surrogate microorganism for in-plant critical control point validation, we compared the rates of thermal inactivation of three bacteria, Enterococcus faecium B2354, Pediococcus parvulus HP, and Pediococcus acidilactici LP, to those of Listeria monocytogenes and Salmonella. Ground beef samples containing 4 and 12% fat were inoculated with E. faecium, L. monocytogenes, and Salmonella Senftenberg 775W and heated at 58, 62, 65, or 68 degrees C. The decimal reduction times (D-values) for E. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
22
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(22 citation statements)
references
References 14 publications
0
22
0
Order By: Relevance
“…E. faecium NRRL B-2354 has been used in the food industry for heat resistance challenge studies and process validation studies as a surrogate for Salmonella and Listeria monocytogenes (33,41), especially for air roasting almonds for Salmonella inactivation (2). In our study, the long-term survival behavior of E. faecium was compared with Salmonella.…”
Section: Discussionmentioning
confidence: 99%
“…E. faecium NRRL B-2354 has been used in the food industry for heat resistance challenge studies and process validation studies as a surrogate for Salmonella and Listeria monocytogenes (33,41), especially for air roasting almonds for Salmonella inactivation (2). In our study, the long-term survival behavior of E. faecium was compared with Salmonella.…”
Section: Discussionmentioning
confidence: 99%
“…Their abundance in human and animal feces, the ease with which they are cultured, and their correlation with human health outcomes in fresh and marine waters have led to their widespread use as tools for assessing recreational water quality worldwide (333,335,(345)(346)(347). The enterococci are most frequently used as fecal indicator bacteria (FIB), or general indicators of fecal contamination, but they are also used as surrogates for pathogens and/or health effects in risk assessment and other modeling applications (61,214,285,303,329,346). Research spanning more than 3 decades, however, has shown that these bacteria are widely distributed in a variety of environmental habitats, even when there is little or no input from human and/or animal fecal sources.…”
mentioning
confidence: 99%
“…Using non-pathogenic strains as biological indicators for evaluation of pathogen responses is an attractive model to avoid human exposure to pathogens [23,24]. Extensive research has been performed to validate L. innocua as a non-pathogenic surrogate of the food-borne pathogen L. monocytogenes [14,25,26].…”
Section: Discussionmentioning
confidence: 99%